Early Childhood Imitation Behavior Towards Tiktok Movements And Speech - Rika Maya Nur Wati; Ida Yeni Rahmawati; Muhammad Azzam Muttaqin (Academia Open, 2026)
General Background: The widespread use of social media platforms such as TikTok has introduced highly engaging short-video content that is frequently accessed by young children. Specific Background: Children aged five to six are in a developmental stage where learning occurs through observation and imitation of visual and auditory stimuli. Knowledge Gap: Previous studies mainly discuss the general presence of TikTok in children’s lives, while limited research explains the specific forms of movements and speech imitated by early childhood learners in school environments. Aims: This study aims to identify the TikTok content watched by children and describe imitation behavior in movements and speech among students at TK BA Aisyiyah Temon. Results: Using a descriptive qualitative case study involving 20 children aged 5–6 years, data from observations, interviews, and documentation show that 14 children demonstrated imitation behavior. Movements such as “kambing mbe,” “walking hap hap hap,” and “tor monitor ketua” were repeatedly performed, while speech imitation appeared through viral phrases spoken without understanding their meaning. Novelty: The study documents specific patterns of viral movement and speech imitation among early childhood learners in a classroom context. Implications: The findings indicate the importance of parental supervision, digital literacy guidance, and collaboration between families and schools in guiding children’s exposure to social media content. Highlights: Viral video gestures were frequently reproduced during play activities. Spoken phrases from online clips were repeated without understanding their meaning. Higher device exposure at home corresponded with stronger mimicry patterns in class. Keywords: Imitation Behavior, Early Childhood, Tiktok, Movement and Speech